Impact of CXCL1 overexpression on growth and invasion of prostate cancer cell. Issue 9 (17th January 2013) - Benelli, Roberto; Stigliani, Sara; Minghelli, Simona; Carlone, Sebastiano; Ferrari, Nicoletta
Abstract BACKGROUND The role of CXCL1 in prostate cancer (PCa) progression has been poorly investigated. A limitation of previous studies is linked to the use of human PCa cell lines PC3 and DU145, producing CXCL8 at levels strongly exceeding CXCL1 levels. Moreover, in mouse models the sharing of CXCR2 receptor by both ligands makes the phenotype induced by CXCL8 and CXCL1 almost indistinguishable. To overcome this problem we used the murine TRAMP‐C2 cell line, not expressing CXCL8 and expressing CXCL1 at low levels. METHODS The effect of CXCL1 overexpression was examined by in vivo subcutaneous tumor studies and in vitro functional assays of invasion and adhesion. Biochemical modifications were evaluated by Western blotting and antibody arrays. RESULTS Our data show that the overexpression of CXCL1 in TRAMP‐C2 cells represses tumor establishment and in situ invasion. In vitro, the main action of CXCL1 expression in TRAMP cells is associated with the perturbation of molecules linked to cell adhesion and migration thus explaining in vivo data. Other in vitro findings also suggest that signaling by CXCL1 might activate a secretory network limiting in vivo tumor growth by reinforcing senescence. Immunohistochemical staining of human PCa, BPH, and normal prostate biopsies strengthen our observations on the mouse model: when expressed, CXCL1 is limited to small areas with faint staining and PCa progression does not rely on CXCL1 expression. CONCLUSION: We could speculate that CXCL1 overexpression acts as a suppressor of malignancy limiting the escape of tumor cells from the primary tumor and reinforcing growth arrest. Prostate 73: 941–951, 2013. © 2013 Wiley Periodicals, Inc.